Proteolytic cleavage of Arabidopsis thaliana phosphoenolpyruvate carboxykinase-1 modifies its allosteric regulation - Rojas, Bruno Ezequiel (2020)
Phosphoenolpyruvate carboxykinase (PEPCK) plays a crucial role in gluconeogenesis. In this work, we analyze the proteolysis of Arabidopsis thaliana PEPCK1 (AthPEPCK1) in germinating seedlings. We found that the amount of AthPEPCK1 protein peaks at 24-48 h post-imbibition. Concomitantly, we observed shorter versions of AthPEPCK1, putatively generated by metacaspase-9 (AthMC9). To study the impact of AthMC9 cleavage on the kinetic and regulatory properties of AthPEPCK1, we produced truncated mutants based on the reported AthMC9 cleavage sites. The Δ19 and Δ101 truncated mutants of AthPEPCK1 showed similar kinetic parameters and the same quaternary structure as the wild type. However, activation by malate and inhibition by glucose 6-phosphate were abolished in the Δ101 mutant. We propose that proteolysis of AthPEPCK1 in germinating seedlings operates as a mechanism to adapt the sensitivity to allosteric regulation during the sink-to-source transition.